REAKTUALISASI PEMIKIRAN EKONOMI ISLAM TENTANG INVESTASI DAN TABUNGAN DI ERA DIGITAL: INTEGRASI ETIKA SYARIAH, LITERASI KEUANGAN, DAN TRANSFORMASI EKONOMI BERKELANJUTAN - Ayu Gumilang Lestari; Wartoyo Wartoyo; Aan Jaelani (Universitas Islam Negeri Sumatera Utara, 2025)
This study reexamines Islamic economic thought on savings and investment in the digital age by combining classical principles and modern financial innovations. Using a qualitative method based on literature review, this study highlights the relevance of the thoughts of Ibn Khaldun, Al-Ghazali, and Muhammad Baqir al-Sadr to contemporary Islamic finance practices. The research findings show that reactualizing investment and savings in the Islamic economy in the digital era requires the integration of sharia ethics, sharia financial literacy, and a sustainability orientation. The thoughts of Ibn Khaldun, Al-Ghazali, and Baqir al-Sadr emphasize the importance of fair and speculation-free wealth circulation. Although the development of sharia fintech and digital instruments has increased financial inclusion, challenges such as low literacy, cybersecurity risks, and the potential for deviation from fatwas remain significant. Therefore, reactualizing sharia values through education and strengthening regulations is key to building an ethical, inclusive, and sustainable digital financial ecosystem.